Influence of glass forming histories on the structural and thermal properties of tellurite glasses - Araujo, E. B. [UNESP]; Idalgo, E. [UNESP] (Soc Glass Technology, 2009)
Tellurite 20Li(2)O-80TeO(2) glasses were prepared with identical nominal composition but with different glass forming histories. Differential scanning calorimetry and x-ray diffraction techniques were used to study the effects of glass forming histories oil the thermal and structural properties of these glasses. It was observed that the investigated properties depend strongly on the glass forming histories. XRD results reveals the crystallisation of the gamma-TeO(2), alpha-TeO(2) and alpha-Li(2)Te(2)O(5) phases in the studied glasses. DSC results suggested that annealing immediately after quenching at temperatures around T(g) and longer times are favorable to produce local ordered regions in the glass without necessarily increasing nuclei number.